Prevalence of Dirofilaria and Hemato-biochemical Effect in Street Dogs of Kathmandu Valley and Siddharthanagar Municipality, Bhairahawa, Nepal (Nepalese Veterinary Journal, 2019)
A cross sectional study was conducted to determine the prevalence of dirofilariosis in street dogs of Kathmandu valley and Siddharthanagar, Rupandehi from January 2019 to March 2019. .Blood sample from 155 dogs of Kathmandu Valley and 150 from Siddharthanagar municipality were collected and examined by Wet Smear, Modified Knott Technique and Buffy Coat methods. PCV value and biochemical parameters were analyzed. Data were analyzed to determine the Prevalence of Dirofilaria and correlation of infections with age, sex and biochemical parameters. The prevalence in Kathmandu valley was 0% (0/156) while the prevalence in Siddharthanagar was 19.33%., while the prevalence in direct smear, buffy coat and modified Knott technique were found to be 16%, 16% and 19.33% respectively. The prevalence were significantly (p